The rev-responsive element negatively regulates human immunodeficiency virus type 1 env mRNA expression in primate cells. - Churchill, M J (1996)
The human immunodeficiency virus type 1 (HIV-1) Rev protein mediates the accumulation of unspliced and singly spliced viral transcripts within the cytoplasm of infected cells, late in the infection cycle, leading to the expression of the viral structural proteins, Gag, Pol, and Env. Rev binds to a complex RNA structure, the Rev-responsive element (RRE), present in all Rev-responsive viral transcripts, relieving their nuclear sequestration. The precise mechanism by which RRE-containing transcripts are retained within the nucleus in the absence of Rev protein is not well understood. We previously demonstrated that the RRE alone plays a crucial role in the nuclear retention of RRE-containing env transcripts in stably transfected Drosophila cells. Here we extend our previous observations and demonstrate that the RRE is a principal determinant of nuclear retention for envelope transcripts in primate cells and, in particular, human CD4+ T cells.